Effect of geometry and thermal mass of Direct-Metal-Laser-Sintered aluminium Heat Exchangers filled with phase change materials on Lithium-Ion cells' passive cooling. (August 2021) - Landini, S.; Delgado-Diaz, W.; Ravotti, R.; Waser, R.; Stamatiou, A.; Worlitschek, J.; O'Donovan, T.S.
Highlights: Direct-Metal-Laser-Sintered (DMLS) aluminium Heat Exchangers (HEX) DMLS HEX filled with Phase Change Materials (PCM) for Li-Ion cells isothermalisation. Effect of PCM mass and HEX geometry on Li-Ion cells isothermalisation. Single discharge and consecutive charge/discharge cycles tests conducted. Abstract: This study investigates the effect of mass and geometry as design parameters of a Lithium-Ion (Li-Ion) cell Thermal Management System (TMS) based on a Direct-Metal-Laser-Sintered (DMLS) structure filled on Phase Change Material (PCM). As part of a TMS, complex heat exchanger geometries are produced using DMLS technique, filled with a PCM, and experimentally tested using an established methodology. The design parameters investigated are PCM mass and DMLS heat exchanger geometry to assess the effects of increased thermal energy storage capacity and enhanced equivalent thermal conductivity respectively on the overall performance of a Li-Ion pouch cell. Constant discharge rate tests and stress sequences are used to reproduce realistic Li-Ion cell operating conditions. It has been shown that all PCM TMS effectively improve the isothermalisation of the cell under a single discharge at rate 3C compared to natural convection and decreased the cell maximum temperature by at least 5 °C. The enhanced heat transfer performance of finned designs further improves the temperature uniformity and decreases the cell maximum temperature. When tested under stress sequences, the TMS characterised by a higher thermal mass maintained functional isothermalisation for 5 cycles; this is an increase of two cycles than for the TMS with a lower thermal mass. By using a Pareto front analysis based on thermal and geometrical variables, specific designs are indicated as the best combination of thermal performance and additional weight for single discharge tests (i.e., intermittent load) and stress sequences (i.e., constant load).